Craniopharyngioma resection by endoscopic endonasal approach versus transcranial approach: A systematic review and meta-analysis of comparative studies - Na, Min Kyun; Jang, Bohyoung; Choi, Kyu-Sun; Lim, Tae Ho; Kim, Wonhee; Cho, Youngsuk; Shin, Hyun-Goo; Ahn, Chiwon; Kim, Jae Guk; Lee, Juncheol; Kwon, Sae Min; Lee, Heekyung (Frontiers in Oncology, 2022)
The transcranial approach (TCA) has historically been used to remove craniopharyngiomas. Although the extended endoscopic endonasal approach (EEA) to these tumors has been more commonly accepted in the recent two decades, there is debate over whether this approach leads to better outcomes. The goal of this systematic review and meta-analysis was to more comprehensively understand the benefits and limitations of these two approaches in craniopharyngioma resection based on comparative studies. We conducted a systematic literature search in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses recommendations using MEDLINE, EMBASE, and the Cochrane Library. A total of 448 articles were screened. Data were extracted and analyzed using proportional meta-analysis. Eight comparative studies satisfied the inclusion criteria. The extent of resection, visual outcomes, and postoperative complications such as endocrine dysfunction and cerebrospinal fluid (CSF) leakage were compared. Eight studies, involving 376 patients, were included. Resection by EEA led to a greater rate of gross total resection (GTR) (odds ratio [OR], 2.42; p = 0.02; seven studies) with an incidence of 61.3% vs. 50.5% and a higher likelihood of visual improvement (OR, 3.22; p < 0.0001; six studies). However, TCA resulted in a higher likelihood of visual deterioration (OR, 3.68; p = 0.002; seven studies), and was related, though not significantly, to panhypopituitarism (OR, 1.39; p = 0.34; eight studies) and diabetes insipidus (OR, 1.14; p = 0.58; seven studies). Although TCA showed significantly lower likelihoods of CSF leakage (OR, 0.26; 95% confidence interval [CI], 0.10–0.71; p = 0.008; eight studies) compared to EEA, there was no significant difference in meningitis (OR, 0.92; 95% CI, 0.20–4.25; p = 0.91; six studies) between the two approaches. When both approaches can completely resect the tumor, EEA outperforms TCA in terms of GTR rate and visual outcomes, with favorable results in complications other than CSF leakage, such as panhypopituitarism and diabetes insipidus. Although knowledge of and competence in traditional microsurgery and endoscopic surgery are essential in surgical decision-making for craniopharyngioma treatment, when both approaches are feasible, EEA is associated with favorable surgical outcomes.